The transuranium people : the inside story - Hoffman, Darleane C. (Imperial College Press ; Distributed by World Scientific, 2000)
In this highly interesting book, three pioneering investigators provide an account of the discovery and investigation of the nuclear and chemical properties of the twenty presently known transuranium elements. The neutron irradiation of uranium led to the discovery of nuclear fission in 1938 and then to the first transuranium element, neptunium (atomic number 93), in 1940. Plutonium (94) quickly followed and the next nine elements completed the actinide series by 1961. Investigation of the chemical properties of the actinides was followed more recently by chemical studies of the first three transactinides - rutherfordium (104), hahnium (105), and seaborgium (106). Recent discoveries have extended the known elements to 112.